Land tenure policy and off-farm employment in rural China - Hongqin Chang; Ping Ai; Yuan Li (IZA Journal of Development and Migration, 2018)
Using the data from the three waves (1995, 2002, and 2008) of the Chinese Household Income Project (CHIP), this paper investigates the impact of land tenure security on farmers' labor market outcomes in rural China. To identify the effect of land tenure security, this paper used difference-in-differences strategy to control for time invariant heterogeneity and a number of observed time-varying economic characteristics for its validity. The paper finds that in response to more security land rights, both women and men increase their probability of wage employment participation.
Keywords: O15; J61; Q15; R23; 330; Land tenure; Off-farm; Rural China